2020
DOI: 10.3390/diagnostics10030167
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Cardiac Troponin T Increase after Participation in a 100 Km Ultra-Marathon

Abstract: Background: Intensive and prolonged exercise leads to a rise of troponin concentration in blood. The mechanism responsible for troponin release during exercise remains ill-defined. The study aim was to search for risk factors of troponin increase after a prolonged endurance competition. Methods: The study included a group of 18 amateurs, healthy volunteers (median age 41.5 years, interquartile range – IQR 36–53 years, 83% male) who participated in a 100 km running ultra-marathon. Information on demographic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Various evidence on the role of miRNAs in lactate dehydrogenase’s (LDH) activity exist, and it is postulated that some miRNAs may aggravate cell injury via LDH action enhancement ( Ge et al, 2019 ). It is established that participation in ultramarathon runs leads to significant elevation in high-sensitivity troponin T (hs-TnT) concentration, although the mechanism of this phenomenon is poorly understood ( Małek et al, 2020 ). Moreover, some miRNAs were found to be independently associated with the increase in hs-TnT levels ( Widera et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various evidence on the role of miRNAs in lactate dehydrogenase’s (LDH) activity exist, and it is postulated that some miRNAs may aggravate cell injury via LDH action enhancement ( Ge et al, 2019 ). It is established that participation in ultramarathon runs leads to significant elevation in high-sensitivity troponin T (hs-TnT) concentration, although the mechanism of this phenomenon is poorly understood ( Małek et al, 2020 ). Moreover, some miRNAs were found to be independently associated with the increase in hs-TnT levels ( Widera et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, several clinical studies on ultra-marathon runners reported that intensive training can be also related to cardiovascular pathological changes [ 36 , 37 , 38 , 39 ]. However, results are contradictory [ 40 ]. Several molecular based studies showed that endurance training may increase oxidative stress, hypoxia and cardiac fibrosis [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among marathon runners, 38-82 % showed an increase in TnT after the race [17,18]. An increase in TnT above the upper reference limit has also been reported in 0-66 % of ultra-marathon participants; however, the increase in ultra-marathon participants is often smaller than that in marathoners [17,19,20]. In light of the abovementioned background studies, the length of a race and running speed seem to be important for potential changes in biochemical signs of cardiac responses.…”
Section: Introductionmentioning
confidence: 99%